Literasi Keuangan dan Faktor Demografi terhadap Resiliensi Keuangan Mahasiswa Fakultas Ekonomi dan Bisnis Universitas Negeri Padang - Dinda Hafiziah Azzahara; Yolandafitri Zulvia (Jurnal Literasi Akuntansi, 2026)
Purpose: This study aims to determine whether there is an influence of financial literacy and demographic factors on the financial resilience of students of the Faculty of Economics and Business, Padang State University. Method: The population in this study were undergraduate students entering the 2022 and 2023 academic years studying at the Faculty of Economics and Business, Padang State University. The sample in this study were undergraduate students from the management, accounting, development economics, and economic education study programs entering the 2022 and 2023 academic years of the Faculty of Economics and Business, Padang State University. The sample size was 135 respondents, using proportional random sampling. The analytical tool used in this study was multiple linear regression analysis with the assistance of SPSS version 27. Finding: The results of this study indicate that financial literacy has a positive and significant effect on students' financial resilience. However, demographic factors (gender, age, academic ability, and residence) did not influence students' financial resilience. Novelty: This study focuses on students of the Faculty of Economics and Business, Padang State University by combining two variables in one comprehensive framework, in contrast to previous studies that examined financial resilience in accounting students and gender factors